An Innocuous Solitary Neck Node: Case Report of an Occult Papillary Thyroid Microcarcinoma Presenting with Nodal Metastasis - Weng, Jiayi; Tay, KonVoi; Ho, Thomas WaiThong; Low, MeiYi (Archives of Clinical and Medical Case Reports, 2021)
Background: Occult primary head and neck cancer constitutes 5-10% of all patients with carcinoma of unknown primary and presents as both a diagnostic challenge and management dilemma to clinicians. We present one case of papillary thyroid microcarcinoma where the only presenting sign was a painless enlarged cervical lymph node, with no evidence of the primary site of malignancy after initial evaluations. Case Presentation: A sixty-five-year-old female patient presented with a two-month history of painless swelling on the left side of the neck with no change in size. Ultrasonography detected a left level V lymph node and a left level IV lymph node with suspicious features for malignancy but did not detect any thyroid nodules. Excision biopsy of the lymph node and bilateral tonsillectomy revealed a diagnosis of metastatic papillary carcinoma with a primary from the thyroid. A repeat focused ultrasonography of the thyroid revealed two nodules. Total thyroidectomy and selective left neck dissection (levels IIVI) were performed. The final diagnosis was multifocal papillary thyroid carcinoma with metastasis to seven out of twenty-four lymph nodes excised. The TMN stage was pT1aN1bM0. The patient was discharged on postoperative day three uneventfully. Adjuvant radioactive iodine was planned for the patient at a dose of 100 mCi at one month postoperatively. Conclusion: Occult primary PTMC presenting as isolated cervical lymphadenopathy and diagnosed only on histology is a rare entity. When initial clinical and radiological evaluations reveal no thyroid abnormalities, FNAC and excision of lymph nodes are useful steps in establishing the diagnosis and primary site of the tumour. Total thyroidectomy with a therapeutic neck dissection is the appropriate next step in treatment for these patients. With postoperative radioactive